Graphical analysis for overall effectiveness management: A graphical method to support operation and maintenance performance assessment. (3rd August 2018) - Viveros Gunckel, Pablo; Kristjanpoller, Fredy; López‐Campos, Mónica; Crespo Márquez, Adolfo; Pascual, Rodrigo
Abstract: This article presents a graphical tool for the monitoring of performance indicators called GAOEM (Graphical Analysis for Overall Effectiveness Management). GAOEM comprehends the main indicators of maintenance and operations management, and it constitutes an adaptation of the overall effectiveness index. GAOEM facilitates control and analysis by using specific indicators in a graphic panel, designed for industries with high investment in physical assets. It also facilitates an efficient reading and interpreting of the data, enriching the analysis, the search for phenomena of interest and improvement opportunities to support the decision making. GAOEM requires 3 categories of input data, which are interventions data, time data, and production/process data. With this information, the basic performance indicators are calculated, being these indicators fundamental for the control and monitoring of the performance level. Later, these indicators will be the basis for calculation of both partial and total performance. GAOEM can be used as a diagnosis, analysis, control and monitoring tool for the indicators of interest at a strategic level, as well as a tool for searching of phenomena typical of a specific stage of the life cycle of assets and also of those conditions resulting from improper operation and/or maintenance, identifying their root causes.